The limits of hospitality?: The role of restorative justice in domestic violence cases - Jokinen, Heidi (Approaching religion, 2020)
While restorative justice is seen as a valuable means for conflict resolution in many kinds of conflict, in the context of domestic violence cases it is still heavily debated. This article posits that the notion of hospitality makes a fruitful contribution to that debate. The urgency of domestic violence against women seems to challenge any hospitable approach between the victim and the offender. However, this article claims that in the light of radical hospitality, restorative justice even in domestic violence cases can become meaningful.